Human hepatoma cell line (Hep G2) cellular response to hypothermic stress with recovery. Induction of Hsp70, Hsp60 and Hsf1 expression. - Rada, Alegna; Merentes, Elizabeth; Merentes, Elizabeth; Rodríguez, Marianela; Rodríguez, Marianela; Anselmi, Guillermo; Anselmi, Guillermo; Mirian Strauss, Mirian Strauss; Mirian Strauss, Mirian Strauss (Investigación Clínica, 2013)
Â The cell response of human HepG2 cells exposed to hypothermia with rewarming was analyzed. Ultrastructural findings in hypothermic stressed cells showed swollen mitochondria, dispersed chromatin, vacuoles and ring-shape nucleolar reorganization. These changes were coupled with significative differences in the induction of Hsp60, inducible Hsp70 and monomeric Hsf1 in all treated samples, but not in Hsc 70 expression. Cellular response to hypothermia could be associated with the synergistic induction of Hsp expression.